Pengaruh Foto Produk Dan Customer Rrview Terhadap Minat Beli Pada E-Commmerce Shopee - Amri, Mila (Jurnal Manajemen, 2025)
This study aims to analyze the impact of product photos and customer reviews on consumer purchase intention on Shopee. A quantitative approach with simple random sampling was employed, targeting the Tangerang population. Data was collected from 172 respondents via questionnaires and analyzed using SPSS. The results indicate that both product photos and customer reviews have a significant positive effect on consumer purchase intention. Informative product photos and reviews boost consumer confidence, thereby strengthening purchasing decisions. This research highlights the importance of high-quality photos and reliable customer reviews in e-commerce marketing strategies to enhance consumer purchase intention on Shopee